2018
DOI: 10.1371/journal.pone.0193024
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock of Moso bamboo (Phyllostachys pubescens) forests along a latitude gradient in the subtropical region of China

Abstract: Latitude is an important factor that influences the carbon stock of Moso bamboo (Phyllostachys pubescens) forests. Accurate estimation of the carbon stock of Moso bamboo forest can contribute to sufficient evaluation of forests in carbon sequestration worldwide. Nevertheless, the effect of latitude on the carbon stock of Moso bamboo remains unclear. In this study, a field survey with 36 plots of Moso bamboo forests along a latitude gradient was conducted to investigate carbon stock. Results showed that the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
2
21
2
1
Order By: Relevance
“…Nutrient stocks of the aboveground biomass in unfertilized plots in this study were 344 kg ha −1 for N, 31 kg ha −1 for P, and 362 kg ha −1 for K. The values were slightly higher than in Moso bamboo forests (N: 274 kg ha −1 , P: 17 kg ha −1 , K: 289 kg ha −1 ) in China [19]. In addition, the C stocks of 48,900 kg ha −1 in this study were within the range (48,310 kg ha −1 -60,580 kg ha −1 ) observed in Moso bamboo stands of the subtropical region in China [20]. Nutrient stocks in roots were significantly higher in the unfertilized plots than those in the fertilized plots, except for the P stocks of roots, whereas the nutrient stocks in rhizomes were not affected by regular fertilization (Table 4).…”
Section: Nutrient Content and Stocks Of Biomass Componentscontrasting
confidence: 45%
See 1 more Smart Citation
“…Nutrient stocks of the aboveground biomass in unfertilized plots in this study were 344 kg ha −1 for N, 31 kg ha −1 for P, and 362 kg ha −1 for K. The values were slightly higher than in Moso bamboo forests (N: 274 kg ha −1 , P: 17 kg ha −1 , K: 289 kg ha −1 ) in China [19]. In addition, the C stocks of 48,900 kg ha −1 in this study were within the range (48,310 kg ha −1 -60,580 kg ha −1 ) observed in Moso bamboo stands of the subtropical region in China [20]. Nutrient stocks in roots were significantly higher in the unfertilized plots than those in the fertilized plots, except for the P stocks of roots, whereas the nutrient stocks in rhizomes were not affected by regular fertilization (Table 4).…”
Section: Nutrient Content and Stocks Of Biomass Componentscontrasting
confidence: 45%
“…DBH growth in fertilized plots could be affected by the increased number of new shoots following fertilizer application [19]. The values of DBH in this study were slightly higher than the range (mean: 8.37-10.12 cm) of Moso bamboo stands (culm density: 3400-4732 culm ha −1 ) in the subtropical region of China [20]. Table 1.…”
Section: Stand and Soil Attributesmentioning
confidence: 58%
“…We began with the construction of a priori model for the multi-group SEM procedure. The priori model was constructed to include all hypothesized causal relationships between BCD and potential driving factors based on the known effects of driving factors and the relationships among driving factors of forest growth and biomass accumulation (Bollen 1989;Shipley 2004;Xu et al 2018aXu et al , 2018b. As shown in Annex 2a of Additional file 1, five driving factors were included in the priori model: stand age, stand coverage, mean annual precipitation, latitude, and elevation.…”
Section: Multi-group Semmentioning
confidence: 99%
“…In addition, as another important geographical factor, latitude may have indirect effect on forest biomass carbon density by affecting plant growth and productivity through temperature and precipitation effects. It was found that the forest biomass carbon density decreased with increasing latitude along the north-south transect of eastern China (Wen and He 2016); while the biomass carbon density of Moso bamboo forests linearly increased with latitude (Xu et al 2018a(Xu et al , 2018b.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation